UJI EFEKTIFITAS BEBERAPA WARNA PERANGKAP BASAH UNTUK MENGENDALIKAN HAMA LALAT BUAH (Bactrocera sp) PADA TANAMAN BELIMBING - Irna Syofia; Nursamsi ,; Heri Indrian (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
The aim of this study was to determine the color type of effective wet traps in controlling pests of fruit flies on starfruit plants by using Group Randomized Design (RAK) Non factorial with 6 treatments and 4 replications. The treatments tested were Methyl eugenol traps + wet without color (P), methyl eugenol traps + Wet blue (Q), methyl eugenol traps wet yellow + (R), methyl eugenol traps wet green + (S), methyl eugenol + red wet traps (T) Methyl eugenol traps wet black + (U). The further testing showed that DMRT + Methyl eugenol traps wet yellow significantly affected catches of fruit flies.Keywords : methyl eugenol, sex feromone,wet trap